2020
DOI: 10.5194/bg-17-683-2020
|View full text |Cite
|
Sign up to set email alerts
|

High-pH and anoxic conditions during soil organic matter extraction increases its electron-exchange capacity and ability to stimulate microbial Fe(III) reduction by electron shuttling

Abstract: Abstract. Soil organic matter (SOM) is redox-active, can be microbially reduced, and transfers electrons in an abiotic reaction to Fe(III) minerals, thus serving as an electron shuttle. The standard procedure to isolate organic matter (OM) from soil involves the use of alkaline and acidic solutions and the separation of humic acids (HAs) and fulvic acids (FAs). This process potentially leads to unwanted changes in SOM chemical and redox properties. To determine the effects of extraction conditions on the redox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…With 5 mmol L –1 , 10 mmol L –1 , 25 mmol L –1 , and 50 mmol L –1 AQDS immobilized in agar, the average ferrihydrite reduction rates were 1.25 ± 0.05 mmol L –1 Fe­(II) d –1 , 1.52 ± 0.16 mmol L –1 Fe­(II) d –1 , 1.76 ± 0.07 mmol L –1 Fe­(II) d –1 , and 1.88 ± 0.11 mmol L –1 Fe­(II) d –1 , respectively (SI Figure S3). During our previous study, we showed that the diffusion coefficient of AQDS was 10 –7 cm 2 s –1 in agar, which is about ten times lower than that in water (10 –6 cm 2 s –1 ). , However, the ferrihydrite reduction rate of the incubations with AQDS immobilized in agar was comparable and in the same order of magnitude than in water (2.36 ± 1.07 mmol L –1 Fe­(II) d –1 ) . These results indicated that other electron-transfer mechanisms existed in addition to diffusion, which enhanced the overall AQDS electron-transfer rate in agar.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…With 5 mmol L –1 , 10 mmol L –1 , 25 mmol L –1 , and 50 mmol L –1 AQDS immobilized in agar, the average ferrihydrite reduction rates were 1.25 ± 0.05 mmol L –1 Fe­(II) d –1 , 1.52 ± 0.16 mmol L –1 Fe­(II) d –1 , 1.76 ± 0.07 mmol L –1 Fe­(II) d –1 , and 1.88 ± 0.11 mmol L –1 Fe­(II) d –1 , respectively (SI Figure S3). During our previous study, we showed that the diffusion coefficient of AQDS was 10 –7 cm 2 s –1 in agar, which is about ten times lower than that in water (10 –6 cm 2 s –1 ). , However, the ferrihydrite reduction rate of the incubations with AQDS immobilized in agar was comparable and in the same order of magnitude than in water (2.36 ± 1.07 mmol L –1 Fe­(II) d –1 ) . These results indicated that other electron-transfer mechanisms existed in addition to diffusion, which enhanced the overall AQDS electron-transfer rate in agar.…”
Section: Resultsmentioning
confidence: 79%
“…32,33 However, the ferrihydrite reduction rate of the incubations with AQDS immobilized in agar was comparable and in the same order of magnitude than in water (2.36 ± 1.07 mmol L −1 Fe(II) d −1 ). 34 These results indicated that other electrontransfer mechanisms existed in addition to diffusion, which enhanced the overall AQDS electron-transfer rate in agar.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Bauer et al, 2009 [56] also claimed the electron donation of NOM to be capable of reducing crystalline minerals such as goethite or hematite phases containing Fe 3+ , where specific interactions between Fe 3+ on the mineral's surface and NOM influences the electron transfer process. In addition, it has been extensively reported [57][58][59] that NOM and iron can form complexes, and the reduction of iron can occur even if the metal is part of the complex; NOM can act as a ligand towards Fe 3+ , and NOM's composition, concentration, aromatic character and presence of complex compounds highly impact the reactivity of the Fe-organic associations [53].…”
Section: Photo-cwpo Under Visible (Vis) Irradiationmentioning
confidence: 99%
“…33−36 We focused our analysis on WEOM extracts as water soluble compounds represent the most bioavailable and dynamic pool of C in soil 37 and reflect bulk SOM composition better than other, more exhaustive extractions, 38,39 which have been shown to bias electrochemical analysis through the formation of redox-active functional groups. 40 We hypothesized that warming-induced changes in WEOM aromaticity would co-vary with overall electron exchange capacity (EEC), while changes in the abundance of phenols and condensed aromatics would correlate with EDC and EAC, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term warming at the site resulted in a decline of fine root biomass, microbial and fungal biomass, ,, and SOM stocks (−60%). , While SOM stocks declined the most in the organic surface horizon, as evident by visible thinning, SOM composition changed most significantly in the underlying mineral horizons . To assess whether these warming-induced changes in SOM composition altered its redox capacity, we analyzed the WEOM from both heated and control soils by electrochemical flow injection analysis ,, and high resolution Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). We focused our analysis on WEOM extracts as water soluble compounds represent the most bioavailable and dynamic pool of C in soil and reflect bulk SOM composition better than other, more exhaustive extractions, , which have been shown to bias electrochemical analysis through the formation of redox-active functional groups . We hypothesized that warming-induced changes in WEOM aromaticity would co-vary with overall electron exchange capacity (EEC), while changes in the abundance of phenols and condensed aromatics would correlate with EDC and EAC, respectively.…”
Section: Introductionmentioning
confidence: 99%